2021
DOI: 10.3390/su13031570
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Environmental Performance of Lemnaminor Cultivated on Agricultural Wastewater Streams—A Practical Approach

Abstract: This study investigated the potential of Lemna minor to valorise agricultural wastewater in protein-rich feed material in order to meet the growing demand for animal feed protein and reduce the excess of nutrients in certain European regions. For this purpose, three pilot-scale systems were monitored for 175 days under outdoor conditions in Flanders. The systems were fed with the effluent of aquaculture (pikeperch production—PP), a mixture of diluted pig manure wastewater (PM), and a synthetic medium (SM). PM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…As a result, duckweed species can be used to effectively remediate wastewater and recycle plant nutrients in accordance with the principles of the circular economy. Ample examples of duckweed‐based nutrient recycling have been published, and these relate to different nutrient‐rich wastewaters, such as farm manure (Dinh et al, 2020; Hu et al, 2019), aquaculture‐industry wastewater (Devlamynck et al, 2021; Paolacci et al, 2021), processing wastewater from the dairy industry (Walsh et al, 2020, 2021), and municipal wastewater (Kotoula et al, 2020). Nutrient recycling involves the use of nutritionally desirable duckweed biomass as feed and/or food for livestock and human consumption (Sree et al, 2015), fertilizer (Ahmad et al, 1990; Chikuvire et al, 2018) or biofuel (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, duckweed species can be used to effectively remediate wastewater and recycle plant nutrients in accordance with the principles of the circular economy. Ample examples of duckweed‐based nutrient recycling have been published, and these relate to different nutrient‐rich wastewaters, such as farm manure (Dinh et al, 2020; Hu et al, 2019), aquaculture‐industry wastewater (Devlamynck et al, 2021; Paolacci et al, 2021), processing wastewater from the dairy industry (Walsh et al, 2020, 2021), and municipal wastewater (Kotoula et al, 2020). Nutrient recycling involves the use of nutritionally desirable duckweed biomass as feed and/or food for livestock and human consumption (Sree et al, 2015), fertilizer (Ahmad et al, 1990; Chikuvire et al, 2018) or biofuel (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Duckweed grown under ideal conditions contains 17.50%–37.00% total protein on a dry weight basis [ 15 ], 59.33% of total carbohydrates, and 7.33% of lipids [ 16 ]. Duckweed has a wider range of essential amino acids [ 17 ] and is rich in macro and micronutrients [ 16 ]. Studies showed that duckweed is one of the potential protein sources that can be easily produced by farmers, and used as supplementary feed to livestock [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This situation calls for alternate management systems to valorize the surplus of waste residues. Therefore, the recycling of nutrients from digestate for production of feed-grade protein creates an opportunity for a circular nutrient economy concept (Devlamynck et al, 2021).…”
Section: Introductionmentioning
confidence: 99%